2019
DOI: 10.1016/j.scitotenv.2018.12.257
|View full text |Cite
|
Sign up to set email alerts
|

Prospects and challenges of concentrated solar photovoltaics and enhanced geothermal energy technologies

Abstract: Prospects and challenges of concentrated solar photovoltaics and enhanced geothermal energy technologies. Stoten (2018),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(46 citation statements)
references
References 62 publications
(21 reference statements)
0
38
0
Order By: Relevance
“…All the achievements recorded so far in the fuel cell technology has been due to continued research on PEM fuel cell and renewable energy in general [149][150][151][152][153][154][155][156][157][158][159][160]. Discussions in this work showed that a comprehensive knowledge of materials and properties is necessary toward choosing the correct preparation method.…”
Section: Future Workmentioning
confidence: 96%
“…All the achievements recorded so far in the fuel cell technology has been due to continued research on PEM fuel cell and renewable energy in general [149][150][151][152][153][154][155][156][157][158][159][160]. Discussions in this work showed that a comprehensive knowledge of materials and properties is necessary toward choosing the correct preparation method.…”
Section: Future Workmentioning
confidence: 96%
“…40,41 Based on the statistics, 82 countries benefit from direct use of geothermal energy, and 26 countries use this energy for power production (ie, 0.3% of the total world electricity was produced from geothermal energy in 2012). 40,41 Based on the statistics, 82 countries benefit from direct use of geothermal energy, and 26 countries use this energy for power production (ie, 0.3% of the total world electricity was produced from geothermal energy in 2012).…”
Section: Geothermal Energymentioning
confidence: 99%
“…Geothermal energy utilization can be considered as a zero-CO 2 energy source and in comparison to wind and solar has this potential to supply an approximately constant and stable load during the day. 40,41 Based on the statistics, 82 countries benefit from direct use of geothermal energy, and 26 countries use this energy for power production (ie, 0.3% of the total world electricity was produced from geothermal energy in 2012). 42,43 The leader countries of geothermal power production in the world are stated in Figure 2.…”
Section: Geothermal Energymentioning
confidence: 99%
“…Finally, traditional fossil fuel energy systems are still more efficient and flexible in generating power than available solar systems. Over the past few years, the chart has been rising to encourage many governments to use green renewable energy sources because they feel the need to reduce dependence on fossil fuels and ensure their economic security …”
Section: Introductionmentioning
confidence: 99%